Constructivist Teaching Strategies in Secondary Science Education: A Systematic Review of Student-Centered and Active Learning Approaches - Cromwell B. Ancla Jr.; Mauricio S. Adlaon (Tecno Scientifica Publisher, 2026)
Constructivist teaching strategies have gained increasing attention in science education because they emphasize student-centered, inquiry-oriented, and active learning experiences. This study presents a systematic review of empirical research on constructivist instructional approaches in secondary science education published between 2019 and 2025. Following the PRISMA 2020 framework, a structured literature search was conducted using Scopus, ERIC, and Google Scholar. Eighty-eight records were initially identified, and after duplicate removal, screening, and eligibility assessment, 43 studies were included in the final qualitative synthesis. The reviewed literature examined several constructivist approaches, including Problem-Based Learning, Inquiry-Based Learning, cooperative learning, guided inquiry laboratory activities, project-based learning, and integrated constructivist instructional models. A thematic synthesis approach was employed to analyze cognitive, affective, and skill-based learning outcomes across the studies. Unlike earlier reviews that mainly focused on single instructional approaches, this review comparatively synthesized multiple constructivist strategies within a unified analytical framework. The findings revealed that constructivist instructional approaches were consistently associated with improvements in academic achievement, conceptual understanding, engagement, critical thinking, science process skills, creativity, collaboration, and motivation. Problem-Based Learning and Inquiry-Based Learning emerged as the most frequently implemented and strongly supported strategies. However, the review also identified important implementation challenges related to instructional scaffolding, teacher preparedness, classroom management, resource limitations, and contextual variation. Some studies further suggested that constructivist approaches did not always produce immediate learning gains when instructional support was insufficient. Overall, the findings indicate that constructivist teaching strategies offer strong potential for improving secondary science education when they are carefully designed and effectively facilitated in classrooms.